TINJAUAN YURIDIS JASA ANGKUTAN UMUM DENGAN APLIKASI BERBASIS TEKNOLOGI INFORMASI (PERSPEKTIF HUKUM BISNIS) - Siti Mariyam (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
The phenomenon of the presence of online transportation both two wheels and four wheels today is growing very rapidly. Many people use this type of transportation with information technology (online) based applications as an option for public transportation currently in Indonesia. Transportation with information technologybased applications is actually the same as other types of public transportation (taxis) but the difference is how to order this transportation that is integrated with the internet so that it makes it easier for people to order. The community feels that they are benefitted by the presence of online transportation because of the easy way of ordering and competitive prices with convenient service. The existence of online transportation is felt to be beneficial for passengers and the public who own capital (cars). For the public, as passengers, it is facilitated by accessing the transportation at relatively cheap prices and good service, meanwhile for the community as owners of capital (cars), they have the opportunity to do business which results in additional income so as to improve welfare for the family. The presence of online transportation, although felt by many people, has many benefits, but as a business activity / business of public transportation services, the existence of online transportation needs to be regulated in a statutory regulation. The regulation is needed to provide legal certainty and protection for drivers, passengers and business people, so that it will create a sense of security, comfort and safety in accordance with the objectives of transportation in accordance with the mandate of legislation.